Inactivation of Cone-Specific Phototransduction Genes in Rod Monochromatic Cetaceans - Springer, Mark S.; Emerling, Christopher A.; Fugate, Noah; Patel, Rachna; Starrett, James; Morin, Phillip A.; Hayashi, Cheryl; Gatesy, John (Frontiers in Ecology and Evolution, 2016)
Vertebrate vision is mediated by two types of photoreceptors, rod and cone cells. Rods are more sensitive than cones in dim light, but are incapable of color discrimination because they possess only one type of photosensitive opsin protein (rod opsin = RH1). By contrast, cones are more important for vision in bright light. Cones also facilitate dichromatic color vision in most mammals because there are two cone pigment genes (SWS1, LWS) that facilitate color discrimination. Cone monochromacy occurs when one of the cone opsins (usually SWS1) is inactivated and is present in assorted subterranean, nocturnal, and aquatic mammals. Rod monochromacy occurs when both cone photoreceptors are inactivated, resulting in a pure rod retina. The latter condition is extremely rare in mammals and has only been confirmed with genetic evidence in five cetacean lineages, golden moles, armadillos, and sloths. The first genetic evidence for rod monochromacy in these taxa consisted of inactivated copies of both of their cone pigment genes (SWS1, LWS). However, other components of the cone phototransduction cascade are also predicted to accumulate inactivating mutations in rod monochromats. Here, we employ genome sequences and exon capture data from four baleen whales (bowhead, two minke whales, fin whale) and five toothed whales (sperm whale, Yangtze River dolphin, beluga, killer whale, bottlenose dolphin) to test the hypothesis that rod monochromacy is associated with the inactivation of seven genes (GNAT2, GNB3, GNGT2, PDE6C, PDE6H, CNGA3, CNGB3) in the cone phototransduction cascade. Cone-monochromatic toothed whales that retain a functional copy of LWS (beluga, Yangtze River dolphin, killer whale, bottlenose dolphin) also retain intact copies of other cone-specific phototransduction genes, whereas rod monochromats (Antarctic minke whale, common minke whale, fin whale, bowhead whale, sperm whale) have inactivating mutations in five or more genes in the cone phototransduction cascade. The only shared inactivating mutations that were discovered occur in the three Balaenoptera species (two minke whales, fin whale), further suggesting that rod monochromacy evolved independently in two clades of baleen whales, Balaenopteroidea and Balaenidae. We estimate that rod monochromacy evolved first in Balaenopteroidea (~28.8 Ma) followed by P. macrocephalus (~19.5 Ma) and Balaenidae (~13.0 Ma).